From Green to Circular Public Procurement in Denmark - Kristensen, Heidi Simone; Alberg Mosgaard, Mette; Remmen, Arne (Ökologisches Wirtschaften - Fachzeitschrift, 2022)
Green procurement is a high priority both in businesses and in government. To develop this strategy towards a holistic Circular Public Procurement, greater institutionalization is necessary.